Synthesis of Alkyl α-Amino-benzylphosphinates by the Aza-Pudovik Reaction; The Preparation of the Butyl Phenyl-H-phosphinate Starting P-Reagent - Bence Bajusz; Dorka Nagy; Regina Tóth; Zsuzsanna Szalai; Ágnes Gömöry; Angéla Takács; László Kőhidai; György Keglevich (Molecules)
Butyl phenyl-H-phosphinate that is not available commercially was prepared from phenyl-H-phosphinic acid by three methods: by alkylating esterification (i), by microwave-assisted direct esterification (ii), and unexpectedly, by thermal esterification (iii). Considering the green aspects, selectivity and scalability, the thermal variation seemed to be optimal. However, there was need for prolonged heating. The butyl phenyl-H-phosphinate, along with the ethyl analogue, was utilized in the synthesis of alkyl (α-alkylamino-arylmethyl-)phenyl phosphinates in the aza-Pudovik reaction with imines obtained from primary amines and substituted benzaldehydes. The aminophosphinates were obtained as diastereomeric mixtures in 65–92% yields. The aza-Pudovik approach was more efficient than the Kabachnik–Fields condensation. Interestingly, one aminophosphinate, the butyl (α-butylamino-benzyl-)phenylphosphinate, was of significant cytotoxic activity on the PANC-1 pancreas cell line. Another derivative, ethyl (α-benzylamino-benzyl-)phenylphosphinate, revealed a selective toxic activity on U266 myeloma cells.